2019
DOI: 10.24925/turjaf.v7i9.1411-1414.2721
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Nutritional Quality of Some Oilseed Meals Through Solid-State Fermentation Using Aspergillus niger

Abstract: This study aimed to investigate the effect of solid-state fermentation on the nutritional composition of cottonseed meal (CSM), sunflower meal (SFM) and hazelnut kernel meal (HKM). In this study, each feedstuff was divided into two treatment groups (unfermented and fermented) with five replicates. Nutritional changes in the feedstuffs were determined by analyzing crude protein, ether extract, ash, crude fiber, neutral detergent fiber, acid detergent fiber contents. Solid-state fermentation had effects on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…These results suggested that solid-state fermentation using A. niger was not enough effective in the substrate with high nutrient content due to the fact that an increase in the cellulose compounds such as ADF, NDF, ADL, hemicellulose and CF. Our results agree with Altop et al (2019) who reported that the corresponding contents of sunflower meal and cottonseed meal increased by A. niger fermentation. Similar results have been reported in the studies on mango kernel (Kayode and Sani, 2008) and sour cherry kernel (Güngör et al 2017).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results suggested that solid-state fermentation using A. niger was not enough effective in the substrate with high nutrient content due to the fact that an increase in the cellulose compounds such as ADF, NDF, ADL, hemicellulose and CF. Our results agree with Altop et al (2019) who reported that the corresponding contents of sunflower meal and cottonseed meal increased by A. niger fermentation. Similar results have been reported in the studies on mango kernel (Kayode and Sani, 2008) and sour cherry kernel (Güngör et al 2017).…”
Section: Resultssupporting
confidence: 93%
“…As such, it can be said that if the feed is rich in other nutrients as well as high CF content, the effect of fermentation may not be efficient on cellulosic ingredients. The results in some studies about the effect of SSF on sunflower meal (Jannathulla et al, 2018;Altop et al, 2019) and TP (Tosun, 2017) did not support this argument. The discrepancies between the results of previous studies and the present study may be attributed to substrate (particle size, initial moisture content and pretreatment), incubation conditions (pH, relative humidity, temperature, agitation and aeration, additional N, P and C supply) and microorganism used in the fermentation (strain, amount and sowing time), as reported by Pandey (2003) and Elibol and Moreira (2005).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This may be due to changes in the ratios of the other nutrients in the nettle. Similarly, Altop et al (2019) reported no changed CP level in cottonseed meal by A. niger solid-state fermentation. Structural carbohydrates such as cellulose, hemicellulose and lignin reduce the nutrient digestibility in feeds because they are difficult to digest by animals (Graminha et al, 2008).…”
Section: Resultsmentioning
confidence: 94%
“…niger 21,39,40 . Later, Altop et al 42 has also found a reduction in NDF, ADF and hemicellulose in hazelnut kernel meal, and in hemicellulose in sunflower meal and cottonseed meal after A . niger pre‐digestion.…”
Section: Beneficial Effects Of a Nigermentioning
confidence: 91%